Vulnerable atherosclerotic plaque - a review of current concepts and advanced imaging - Špaček, Miloslav; Zemánek, David; Hutyra, Martin; Sluka, Martin; Táborský, Miloš (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2018)
Atherosclerosis is the most common cause of both carotid and coronary steno-occlusive disease. Rupture of an atherosclerotic plaque may lead to the formation of an overlying thrombosis resulting in complete arterial occlusion or downstream embolism. Clinically, this may manifest as a stroke or acute myocardial infarction, the overall leading causes of mortality and disability in developed countries. In this article, we summarize current concepts of the development of vulnerable plaque and provide an overview of commonly used imaging methods that may suggest/indicate atherosclerotic plaque vulnerability.
Keywords: infarkt myokardu; cévní mozková příhoda; lidé; Coronary Angiography; Disease Progression; Plaque, Atherosclerotic; Embolism; arteriae carotides; ateroskleróza; Humans; embolie; Atherosclerosis; Carotid Arteries; progrese nemoci; Myocardial Infarction; aterosklerotický plát; Stroke; koronární angiografie